Unaccusative verbs in Modern Standard Arabic - Alonini, Thana Mahmood (Saudi Journal of Language Studies, 2023)
PurposeThe purpose of this research was to analyze the unaccusative verb in Modern Standard Arabic (MSA) within the framework of MP in order to answer the research question: How does the single argument of an unaccusative verb, that carries the theme theta role and is generated in the object position, receive a nominative case without moving to the [Spec, vP], which is the base subject position?Design/methodology/approachThe analysis in the paper was based on the framework of Minimalist Program (MP) which was proposed by Chomsky (2000). MP concerns economy, simplicity and efficiency in the connection between sound and meaning. Essentially, Chomsky (2000) proposes that faculty of language (FL) contains a computational system that interfaces with external systems, sensorimotor systems and systems of thought. The computational system is based on three operations. The first operation is merge, which combines two syntactic objects to form a new one. It is presented in binary branches that project a hierarchical level. The second operation is agree which establishes syntactic relation for case assignment and agreement. The final operation is move, which composes merge and agree.FindingsThe analysis demonstrated that the sole argument of an accusative verb receives the nominative case in situ. This is due to Locality of Matching in which the agreement holds between the [nom] case on T and NP in internal argument of VP. This is because there is no intervening NP between T and the sole argument in internal argument of VP, which is a base object position.Originality/valueThis research shows that the single argument of the unaccusative verb receives the nominative case in situ. This analysis observes the economic considerations of MP as well as respects the UTAH hypothesis, which rules out the structures where the theme asymmetrically appears as a specifier or a complement.